Responsible dynamics: From sustainable development to the challenge of sustainability - Nomen Ribé, Rosa (Razón y fe, 2022)
This article is a look from science and engineering to the ecclesial reflection on integral ecology. The study and deep analysis made by the author of the evolution of the Social Doctrine of the Church together with the concern for the environment, shows a constant dialogue between ecclesial entities and international organizations until the encyclical Laudato si’, which gives a fundamental role to education and spirituality in the care of the common home.
Keywords: sustainable development; sustainability; integral ecology; Catholic Social Teaching; education; spirituality; Laudato si’